Islamophobia or the Freedom of Expression? Exploring the Coverage of Quran Burning Incidents in International Media - Ghauri, Dr.Muhammad Junaid (Journal of Peace, Development and Communication, 2024)
Desecration of the Holy Quran has become a serious global concern in recent years. On the one hand, burning the Holy book of Muslims falls under the category of blasphemy, on the other hand, this act is permissible under the right of freedom of expression. There is an abundance of research findings that prove the connection between Quran burning and Islamophobia. In light of such findings, this research seeks to explore and analyze the discourses produced by Al Jazeera, The Guardian, The New York Times, Time of India, and The Nation in the aftermath of the 2023 Quran burning incidents in Sweden. The researcher has attempted to discover whether the selected news outlets produced the discourse of ‘Islamophobia’ or ‘freedom of expression’ in their coverage of the incidents. Employing the quantitative and qualitative content analysis, the researcher has found that Al Jazeera, The New York Times, Time of India, and The Nation have condemned the incidents by rejecting the Swedish and ‘far-right’ political argument of freedom of expression to defend the burning of Holy Quran. These news outlets have warned that such incidents would increase Islamophobia in the Western societies. However, The Guardian has remained ‘neutral’ in its editorials by raising questions on the ‘furious response’ from the Muslim world and by questioning the Swedish government’s policy toward the incidents.